AI-driven high-throughput droplet screening of cell-free gene expression - Zhu, Jiawei; Meng, Yaru; Gao, Wenli; Yang, Shuo; Zhu, Wenjie; Ji, Xiangyang; Zhai, Xuanpei; Liu, Wan-Qiu; Luo, Yuan; Ling, Shengjie; Li, Jian; Liu, Yifan (Nature communications, 2025)
Cell-free gene expression (CFE) systems enable transcription and translation using crude cellular extracts, offering a versatile platform for synthetic biology by eliminating the need to maintain living cells. However, Such systems are constrained by cumbersome composition, high costs, and limited yields due to numerous additional components required to maintain biocatalytic efficiency. Here, we introduce DropAI, a droplet-based, AI-driven screening strategy designed to optimize CFE systems with high throughput and economic efficiency. DropAI employs microfluidics to generate picoliter reactors and utilizes a fluorescent color-coding system to address and screen massive chemical combinations. The in-droplet screening is complemented by in silico optimization, where experimental results train a machine-learning model to estimate the contribution of the components and predict high-yield combinations. By applying DropAI, we significantly simplified the composition of an Escherichia coli -based CFE system, achieving a fourfold reduction in the unit cost of expressed superfolder green fluorescent protein (sfGFP). This optimized formulation was further validated across 12 different proteins. Notably, the established E. coli model is successfully adapted to a Bacillus subtilis -based system through transfer learning, leading to doubled yield through prediction. Beyond CFE, DropAI offers a high-throughput and scalable solution for combinatorial screening and optimization of biochemical systems. Cell-free gene expression (CFE) systems are often constrained by numerous biochemical components required to maintain biocatalytic efficiency. Here, the authors propose a droplet-AI combined approach to perform high-throughput and efficient combinatorial screening of CFE. This work led to simplified CFE systems with improved yield and cost-effectiveness.